KEANEKARAGAMAN TUMBUHAN MONOKOTIL DI KAMPUS UNIVERSITAS NEGERI PADANG - Rahaditha Dwi Hisana; Moralita Chatri (Universitas Cokroaminoto Palopo, 2026)
Plant diversity plays an important role in maintaining environmental balance, particularly in urban areas. Universitas Negeri Padang has considerable potential for plant diversity, especially within the monocotyledonous plant group (Monocotyledonae). This study aimed to identify and describe the diversity of monocot plant species in the campus environment based on their morphological characteristics. The research employed a descriptive method through field observations by recording morphological traits, including growth habit, stem, leaves, and reproductive organs. Species identification was carried out using botanical literature and taxonomic references, while data were analyzed descriptively based on taxonomic levels. The results showed that 24 species of monocot plants were identified, belonging to 12 families and 5 orders, namely Arecales, Asparagales, Poales, Zingiberales, and Alismatales. The dominant families included Arecaceae, Araceae, Asparagaceae, and Poaceae. The identified species exhibited morphological variations in leaf structure, stem, root system, and reproductive organs. This diversity reflects the relationship between morphological characteristics and environmental conditions, and also provides educational value as a learning resource in plant morphology and taxonomy studies.